KONTRIBUSI PETANI PEREMPUAN UNTUK MENINGKATKAN PENDAPATAN RUMAH TANGGA DAN PENGAMBILAN KEPUTUSAN BUDIDAYA PADI DI KECAMATAN KUALA KAMPAR KABUPATEN PELALAWAN - Ridho Ary Satria; Roza Yulida; Yulia Andriani (Fakultas Pertanian, Universitas Riau, 2021)
The purpose of this study was to (1) find out the women farmers’ profile in the study area, (2) analyze the contribution of women farmers to household income, (3) find out the process and role of women farmers decision making in paddy farming. The method used in this research is survey method with technique of sample selection by Purposive Sampling method. The number of respondents is 40 respondents. The results showed that the characteristics of women aged 15-55 years old with formal education to junior high school, the most experience for 5-10 years, almost all respondents have the number of dependents of families as many as 1-3 people and no toddlers, the land area ranges from 0.5 -2 Ha, and more than 50% of respondents have main occupations as farmers. The contribution of women farmers' income to household income is 11.69%. Decision making in farming is done equally (husband and wife) with the average score of 3.09 and non-farming decision making done by his own wife with an average score of 1.74